STRATEGI PENINGKATAN PEMASARAN PRODUK BODY SCRUB DI PT. ARJUNA YOGA SAKTI DENPASAR - Tricahyani, Ida Ayu Komang; Wrasiati, Luh Putu; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2019)
This study aims to: 1) analysing internal factor (strengths and weakness) and external factor (opportunity and threats) in the marketing of body scrub product by PT. Arjuna Yoga Sakti; 2) formulating alternative strategy which can be used on body scrub by PT. Arjuna Yoga Sakti; 3) establish a priority strategy for increasing the marketing for body scrub product by PT. Arjuna Yoga Sakti. Business development strategy is determind by using SWOT (Strenght, Weakness, Opportunities and Threats) matrix analysis, supported by quantitative analysis was using matrix EFE, IFE, IE and QSPM. The result showed that the weight value for matrix Internal Factor Evaluation (IFE) was 3,23 (strong position) and External Factor Evaluation (EFE) was 2,53 (relatively moderate). In the Matrix Internal External (IE) strategy that must be done was to grow and establish strategies (growth and build), which consist of an intensive strategy (market penetration, market development and product development) or integrative strategies (backward integration, forward integration and integration horizontal). The priority strategy that can be applied for body scrub by PT. Arjuna Yoga Sakti is to feature the product advantages against other products and to create a social media platform as well as website about body scrub. Keywords : Body scrub, SWOT, QSPM and PT. Arjuna Yoga Sakti